Incorporación y aprehensión de saberes sobre plantas útiles a partir del juego: prácticas de extensión en botánica aplicada - Pochettino, María Lelia (2011)
Taking as a starting point the conception that universitary extension, in conjunction with research and teaching, is one of the basis of modern university, we develop practices that relate our researches on applied ethnobotany with teaching-learning process in Economic Botany, and the application of this knowledge to the resolution of everyday problems. We present the results of an experience, devoted to children and teenagers that are hospitalized, that links, through different games, plants of customary use with current wisdoms in different contexts.